Power of Pixels: Examining the Influence of Digital Tactics on Modern Elections and Political Campaigning - Bejko, Lorenca (Formosa Journal of Multidisciplinary Research, 2024)
This essay tech's swing at selecting and crusades, with a aim on digital strategies and their impacts. It plunges into how developments in tech acquire changed the landscape of campaigning and explores the changing ways that politicians work applied sciences instruments to hit voters. The analyze additionally analyzes the likely outcomes of those strategies, adding issues about elector maneuvering and secrecy breaches. This essay aims to provide a comprehensive comprehension of the intersection between tech and policies in today's society through an informative method. It delves into digitals schemes slippery slopes and their outcomes, traveling from how advancements in computing have revolutionized the realm of campaigning to the potential perils of these tactics, like issues about manipulation of the voter base and violations of privacy defenses. The study also scrutinizes the changing ways politicians surf that ongoing digital sea to contact constituents. Through an knowledgeable technique, this essay goals to offer a complete understanding of the meeting between engineering and politics in today's international the place techniques waves continuously roll onto the shore, reworking strategies and concerns. It takes readers out on that digitally choppy sea and back along to analyze tech's effect on elections and campaigns drift whereas shielding against unintended riptides of misunderstanding.